PENGARUH IMPOR DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI - Mutiara Arlina Rahmadani; Fitra Annisa; Dio Kurniawan; Jolianis Jolianis (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Economic growth is the main indicator of a country's progress and development, measured through the level of per capita income which can increase the welfare and prosperity of society. The purpose of this study is to determine and analyze the influence of imports and investment on Indonesia's economic growth, both partially and simultaneously. Data collection used documentation, with data sources obtained from Statistics Indonesia (BPS) and the World Bank for the period 1989-2024. Data analysis was conducted using multiple regression methods. The results indicate that imports and investment do not have a significant influence on economic growth, either partially or simultaneously. This indicates that high or low imports and investment do not affect economic growth. One cause is unequal economic growth due to disparities between urban and rural areas, as well as between western and eastern Indonesia. This finding indicates that these variables are influenced by other, more dominant factors, thus not having a strong enough impact on national economic growth. This study suggests the need for more in-depth study of other variables that can influence economic growth and the importance of more focused policies to increase the contribution of imports and investment. Other factors include infrastructure, macroeconomic conditions (inflation, interest rates), economic diversification, innovation, and technology.